Teaching for Excellence and Equity Analyzing Teacher Characteristics, Behaviors and Student Outcomes with TIMSS - Burroughs, Nathan (IEA Research for Education, 2019)
This open access book examines the interrelationship of national policy, teacher effectiveness, and student outcomes with a specific emphasis on educational equity. Using data from the IEA's Trends in International Mathematics and Science Study (TIMSS) conducted between 1995 and 2015, it investigates grade four and grade eight data to assess trends in key teacher characteristics (experience, education, preparedness, and professional development) and teacher behaviors (instructional time and instructional content), and how these relate to student outcomes. Taking advantage of national curriculum data collected by TIMSS to assess changes in curricular strategy across countries and how these may be related to changes in teacher and student factors, the study focuses on the distributional impact of curriculum and instruction on students, paying particular attention to overall inequalities and variations in socioeconomic status at the student and country level, and how such factors have altered over time. Multiple methods, including regression and fixed effects analyses, and structural equation modelling, establish the evolution of these associations over time.